TINGKAT PELAYANAN SERTA KETERSEDIAAN SARANA DAN PRASARANA PEJALAN KAKI DI PANTAI LOSARI KOTA MAKASSAR - Ishak, Syarifuddin (Jurnal Transportasi, 2012)
This study aims to analyze the availability and level of service of the infrastructure for pedestrians at Jalan Somba Opu and Jalan Penghubung, in the city of Makassar. The method used is qualitative interpretation based on the interpretation of actual conditions in the field. Investigations were made at three observation points, i.e point A, point B, and point C. The results showed that the maximum level of service for pedestrianinfrastructure was found in the observation point B. The availability of pedestrian infrastructure in all three observation points A, B, and C are still meeting the needs of road users. Pavement surface condition is still good with continuous connectivity.Keywords: pedestrian infrastructure,level of service, continuous connectivity.